In Vivo and In Vitro Evidence that TtgV Is the Specific Regulator of the TtgGHI Multidrug and Solvent Efflux Pump of Pseudomonas putida - Rojas, Antonia (American Society for Microbiology, 2003)
The TtgGHI efflux pump of Pseudomonas putida DOT-T1E plays a key role in the innate and induced tolerance of this strain to aromatic hydrocarbons and antibiotics. The ttgGHI operon is expressed constitutively from two overlapping promoters in the absence of solvents and at a higher level in their presence, but not in response to antibiotics. Adjacent to the ttgGHI operon is the divergently transcribed ttgVW operon. In TtgV-deficient backgrounds, although not in a TtgW-deficient background, expression of the ttgGHI and ttgVW operons increased fourfold. This suggests that TtgV represses expression from the ttgG promoters and controls its own. TtgW plays no major role in the regulation of expression of these promoters. Primer extension revealed that the divergent ttgG and ttgV promoters overlap, and mobility shift assays indicated that TtgV binds to this region with high affinity. DNaseI footprint assays revealed that TtgV protected four DNA helical turns that include the −10 and −35 boxes of the ttgV and ttgG promoters.